2009
DOI: 10.1074/jbc.m809244200
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus NS5A Protein Is a Substrate for the Peptidyl-prolyl cis/trans Isomerase Activity of Cyclophilins A and B

Abstract: We report here a biochemical and structural characterization of domain 2 of the nonstructural 5A protein (NS5A) from the JFH1 Hepatitis C virus strain and its interactions with cyclophilins A and B (CypA and CypB). Gel filtration chromatography, circular dichroism spectroscopy, and finally NMR spectroscopy all indicate the natively unfolded nature of this NS5A-D2 domain. Because mutations in this domain have been linked to cyclosporin A resistance, we used NMR spectroscopy to investigate potential interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
196
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 157 publications
(227 citation statements)
references
References 69 publications
25
196
1
2
Order By: Relevance
“…We previously assigned the spectra of the D2 and D3 domains of HCV NS5A when isolated in solution (53,56,57,67). To monitor by NMR spectroscopy the effects induced by NS5B ⌬21 on the spectrum of NS5A-D2 (or NS5A-D3), we mixed at equimolar concentrations (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously assigned the spectra of the D2 and D3 domains of HCV NS5A when isolated in solution (53,56,57,67). To monitor by NMR spectroscopy the effects induced by NS5B ⌬21 on the spectrum of NS5A-D2 (or NS5A-D3), we mixed at equimolar concentrations (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Region C is different, as it carries besides the three negatively charged residues also four positively charged residues (four Arg). Although we previously showed that the D2 domain is essentially unfolded and that this property is conserved across HCV genotypes (53)(54)(55)67), we reanalyzed the experimental 13 C NMR chemical shifts corresponding to the C ␣ and C ␤ atoms of NS5A-D2 (Biological Magnetic Resonance Bank accession number 16165 (53)) with the SSP (secondary structure propensities) program (68). This novel algorithm detected a residual secondary structure in the three interaction regions of NS5A-D2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations